2019
DOI: 10.4103/ortho.ijortho_451_18
|View full text |Cite
|
Sign up to set email alerts
|

Cup Alignment Change after Screw Fixation in Total Hip Arthroplasty

Abstract: Background: Cup malalignment increase impingement, dislocation, cup migration, and polyethylene wear. Screw fixation for enhanced stability is the preferred option in cases of doubtful primary cup stability. There have been few studies about alignment changes after screw fixation, which may be another cause of cup malalignment. This study aimed to evaluate cup alignment change after screw fixation. Materials and Methods: Patients undergoing imageless navigation total hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Then a variety of inflammatory factors are released from macrophages, causing osteoclast activation and osteoblast inhibition [ 35 , 42 ]. It has been suggested that changes in cup alignment after screw fixation might affect the wear of acetabulum components [ 43 ]. Our results showed that there was no difference in wear rate between the acetabular component with and without screws.…”
Section: Discussionmentioning
confidence: 99%
“…Then a variety of inflammatory factors are released from macrophages, causing osteoclast activation and osteoblast inhibition [ 35 , 42 ]. It has been suggested that changes in cup alignment after screw fixation might affect the wear of acetabulum components [ 43 ]. Our results showed that there was no difference in wear rate between the acetabular component with and without screws.…”
Section: Discussionmentioning
confidence: 99%
“…All the measurements were based on the anatomical reference coordinate system that was built based on the anterior pelvic plane (APP). [ 15 , 35 , 38 ] The APP comprising both anterior superior iliac spines (ASIS) and both pubic tubercles were defined as the coronal plane. The sagittal plane was normal to the vector passing through the bilateral ASISs.…”
Section: Methodsmentioning
confidence: 99%
“…[ 11 , 12 ] To emphasize this idea, Dubousset even referred to the pelvis as the “pelvic vertebra.” [ 13 , 14 ] The acetabular orientation is a determinant of both native joint pathology and complications of the artificial joints. [ 15 18 ] The acetabular orientation is often described in 2 different coordinate systems. As the functional acetabular coordinate system is described in that of the whole body, the functional acetabular orientation in the native joint or the acetabular cup in the replaced joint is inherently influenced by the pelvic orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram revealed that the use of more than 4 screws increased the risk of refurbishment. When the stability of the acetabular cup is compromised, screw xation is recommended [32].…”
Section: Discussionmentioning
confidence: 99%